Report of the Sub-Group I (Chemical and Fertilizer Minerals) of the Working Group on Non-metallic (Industrial) Minerals Constituted by Planning Commission - Planning Commission (Planning Commission, 1984)
The Planning Commission constituted a Working Group on Non-metallic (industrial) Minerals vide O.M.No. I&M-3 (28)/83 dated the 25th July, 1985. Under this Working Group four Sub-groups were set up to cover different groups of minerals as follows :1. Sub-group I Chemical and Fertilizer, minerals 2. Sub-group II - Flux and Construction Minerals 5. Sub-group III - Refractory Minerals 4. Sub-group IV - High value and Export Potential Minerals/Metals.
Planning Commission, Government of India